Nitrogen-doped titanium dioxide supported on activated carbon for synergistic removal of aqueous organic pollutants - Yap, Pow Seng (2012)
In recent years, increasing global water scarcity has resulted in intense research to improve the quantity and quality of drinking water. Adsorption via activated carbon (AC) is a proven technology for water treatment and reclamation, while heterogeneous photocatalysis using titanium dioxide (TiO2) is highly energy-efficient in degrading and mineralizing various recalcitrant organic pollutants. Thus, the coupled adsorption-solar photocatalysis processes potentially present an environmentally-friendly and cost-effective treatment technology for water reclamation and reuse. This study therefore focused on developing a novel bifunctional adsorptive-photocatalytic material which was photoexcitable under solar light irradiation. In this study, various types of nitrogen-doped TiO2 supported on powdered AC (N-TiO2/AC) composites were synthesized via the modified sol-gel techniques. These include the composites prepared via single-stage calcination, two-stage calcination, and also facile techniques incorporating commercial titania P25 (N-P25-TiO2/AC). The composites were characterized using X-ray diffraction (XRD), porosimetry, UV-Vis spectrophotometry, electrophoretic mobility measurement, Fourier transform infrared (FTIR), X-ray photoelectron spectroscopy (XPS), scanning electron microscopy coupled with energy-dispersive X-ray (SEM/EDX), and transmission electron microscopy (TEM). Three aqueous recalcitrant organic pollutants of varying molecular properties, namely bisphenol-A (BPA), sulfamethazine (SMZ), and clofibric acid (CFA), were chosen as the model pollutants in this study.